Temporal and spatial distribution of male and female morphotypes of Macrobrachium rosenbergii (de Man) in Vembanad Lake - Harikrishnan, M; Kurup, B Madhusoodana (Indian Journal of Fisheries, 2011)
The exploited stock of Macrobrachium rosenbergii in Vembanad Lake were examined thoroughly during 1994-‘96 period in order to find out temporal and spatial variations, if any, in the availability of male and female morphotypic forms. Blue clawed morphotypes of both sexes outnumbered the orange clawed ones during both years, while small males and small females constituted only an insignificant proportion during 1994-‘95 (0.13 and 0.15% respectively). With regard to temporal availability, a glaring dominance of orange clawed morphotypes during January to August and a subsequent predominance of blue clawed morphotypes from September to December were also encountered. In general, the predominance of blue clawed morphotypes were quite discernible in all zones, however, orange clawed morphotypes of both sexes could also be observed in significant percentages in upstream and riverine areas in contras to downstream areas.